COVID and animal trials: A systematic review - Muhamood Moothedath; Muhaseena Muhamood; Yadnit S Bhosale; Aseem Bhatia; Pranav Gupta; Medapati Rama Haranadha Reddy; Rahul V C Tiwari (Wolters Kluwer Medknow Publications, 2021)
Extensive work is being done to form targeted drugs against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection; however, it is imperative to have a safe and effective vaccine against the same to win the war against this pandemic. For creating an efficacious vaccine, a proper animal model needs to be selected which can have an acceptable similarity of response as well as effects when administered to humans. For the present research, extensive search was conducted in MEDLINE and bioRxiv and medRxiv servers which were published in the English language from January 1, 2020, to August 20, 2020. Search terms included animal models, SARS-CoV-2, COVID-19, immune response against coronavirus, nonhuman primates, mice, ferrets, and macaques. In our study, creating an adequate immune response mimicking the response as in humans, as the endpoint, was considered as inclusion criterion while assessment of any additional therapies like safety as well as minimal tolerable dose using animal models as well as formation of adequate sample size of these models against COVID-19 was not considered. In our search, 163 articles were shortlisted, of them only 20 articles were finally included in our study which addressed to our inclusion and exclusion criterion. Our research articles focused on nonhuman primates, mice, hamsters, ferrets, cats, and dogs, with the main goal to investigate the role of animal models in the pathogenesis of COVID-19. It was evident in our research that animal models only mimic limited signs and symptoms experienced in COVID infection as compared to infections in humans. However, they are still essential to understand the pathogenesis, transmissibility of viral particles, and vaccine testing.